Health status, geriatric syndromes and prescription of oral anticoagulant therapy in elderly medical inpatients with atrial fibrillation. Issue 3 (28th January 2016) - Bo, Mario; Sciarrillo, Irene; Maggiani, Guido; Falcone, Yolanda; Iacovino, Marina; Grisoglio, Enrica; Fonte, Gianfranco; Grosjean, Simon; Gaita, Fiorenzo
Abstract : Aim: The aim of the present study was to investigate the prevalence of geriatric syndromes among older medical inpatients with atrial fibrillation, and their association with use of vitamin K antagonists. Methods: A retrospective study of patients aged ≥65 years discharged with a diagnosis of atrial fibrillation from the Acute Geriatric Ward was carried out. Stroke and bleeding risk were evaluated according to the CHA2 DS2 ‐VASC and HAS‐BLED scores. Comorbidity, cognitive status, functional autonomy and contraindications to vitamin K antagonists were also considered. Results: Atrial fibrillation was documented in 1078 of 3650 patients (29.5%, mean age 83.4 ± 6.6 years, 60.3% women). Contraindications to vitamin K antagonists were documented in 24.9% of patients. Prescription of vitamin K antagonists at discharge was 37.8% and 47.9%, in the overall sample and in those without contraindications, respectively. In the overall sample, prescription of vitamin K antagonists was associated with younger age, permanent/persistent atrial fibrillation, home discharge, less comorbidity, higher hemoglobin levels, better functional independence, known atrial fibrillation at admission and lower HAS‐BLED score. Among patients without contraindications to vitamin K antagonists, their use at discharge was independently associated with younger age, permanent/persistent atrial fibrillation, home discharge, higher hemoglobin levels and CHA2DS2‐VASC score, better functional autonomy, and greater number of drugs. Conclusions: We showed a high prevalence of atrial fibrillation among older medical inpatients, who have a poor health status and a high prevalence of geriatric syndromes. Vitamin K antagonists were prescribed in less than half of the patients; underuse was mainly accounted for by a high prevalence of comorbidities/contraindications, poor health status and limited functional autonomy.Geriatr Gerontol Int 2017; 17: 416–423.